Targeted genomic capture and massively parallel sequencing to identify genes for hereditary hearing loss in middle eastern families - Brownstein, Zippora; Friedman, Lilach M; Shahin, Hashem; Oron-Karni, Varda; Kol, Nitzan; Rayyan, Amal Abu; Parzefall, Thomas; Lev, Dorit; Shalev, Stavit; Frydman, Moshe; Davidov, Bella; Shohat, Mordechai; et al. (Genome biology, 2011)
Background Identification of genes responsible for medically important traits is a major challenge in human genetics. Due to the genetic heterogeneity of hearing loss, targeted DNA capture and massively parallel sequencing are ideal tools to address this challenge. Our subjects for genome analysis are Israeli Jewish and Palestinian Arab families with hearing loss that varies in mode of inheritance and severity. Results A custom 1.46 MB design of cRNA oligonucleotides was constructed containing 246 genes responsible for either human or mouse deafness. Paired-end libraries were prepared from 11 probands and bar-coded multiplexed samples were sequenced to high depth of coverage. Rare single base pair and indel variants were identified by filtering sequence reads against polymorphisms in dbSNP132 and the 1000 Genomes Project. We identified deleterious mutations in CDH23, MYO15A, TECTA, TMC1 , and WFS1 . Critical mutations of the probands co-segregated with hearing loss. Screening of additional families in a relevant population was performed. TMC1 p.S647P proved to be a founder allele, contributing to 34% of genetic hearing loss in the Moroccan Jewish population. Conclusions Critical mutations were identified in 6 of the 11 original probands and their families, leading to the identification of causative alleles in 20 additional probands and their families. The integration of genomic analysis into early clinical diagnosis of hearing loss will enable prediction of related phenotypes and enhance rehabilitation. Characterization of the proteins encoded by these genes will enable an understanding of the biological mechanisms involved in hearing loss.